Carrier Free Photodynamic Synergists for Oxidative Damage Amplified Tumor Therapy. Issue 40 (4th September 2021) - Li, Xin‐Yu; Deng, Fu‐An; Zheng, Rong‐Rong; Liu, Ling‐Shan; Liu, Yi‐Bin; Kong, Ren‐Jiang; Chen, A‐Li; Yu, Xi‐Yong; Li, Shi‐Ying; Cheng, Hong
Abstract: Tumor cells adapt to excessive oxidative stress by actuating reactive oxygen species (ROS)‐defensing system, leading to a resistance to oxidation therapy. In this work, self‐delivery photodynamic synergists (designated as PhotoSyn) are developed for oxidative damage amplified tumor therapy. Specifically, PhotoSyn are fabricated by the self‐assembly of chlorine e6 (Ce6) and TH588 through π–π stacking and hydrophobic interactions. Without additional carriers, nanoscale PhotoSyn possess an extremely high drug loading rate (up to 100%) and they are found to be fairly stable in aqueous phase with a uniform size distribution. Intravenously injected PhotoSyn prefer to accumulate at tumor sites for effective cellular uptake. More importantly, TH588‐mediated MTH1 inhibition could destroy the ROS‐defensing system of tumor cells by preventing the elimination of 8‐oxo‐2′‐deoxyguanosine triphosphate (8‐oxo‐dG), thereby exacerbating the oxidative DNA damage induced by the photodynamic therapy (PDT) of Ce6 under light irradiation. As a consequence, PhotoSyn exhibit enhanced photo toxicity and a significant antitumor effect. This amplified oxidative damage strategy improves the PDT efficiency with a reduced side effect by increasing the lethality of ROS without generating superabundant ROS, which would provide a new insight for developing self‐delivery nanoplatforms in photodynamic tumor therapy in clinic. Abstract : Carrier free photodynamic synergists are developed for oxidative damage amplified tumor therapy by destroying the reactive oxygen species (ROS)‐defensing system without generating excessive ROS, which shed light on the development of self‐delivery nanoplatforms for efficient photodynamic therapy by utilizing the limited oxygen in hypoxic tumors.